PENGARUH MARKETING VIRAL DAN INFLUENCER TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING DALAM APLIKASI TIKTOK SHOP - Wiyanti, Lilia Nungky Ebita (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to determine the effect of viral marketing and influencers on purchasing decisions for scarlett whitening products in the tiktok shop application, a case study of the people of Kediri Regency. This research was conducted through a quantitative approach using primary data in the form of a questionnaire. The sample used was 30 respondents with a simple random sampling method. Data analysis techniques in the form of descriptive statistics, classical assumption test, multiple linear regression, determinant coefficients and hypothesis testing. The results showed that viral marketing had a significant positive effect on purchasing decisions for scarlet whitening products. It was proved by a significance value of 0.48. Influencers have a significant positive effect on purchasing decisions for scarlet whitening products. This is evidenced by a significance value of 0.000, and Viral Marketing and Influencers have a simultaneous effect on purchasing decisions for scarlet whitening products. This is evidenced by the Fcount value of 113,131 and the significance value of 0.000.